Is Office Laryngoscopy an Aerosol-Generating Procedure? - Rameau, Anaïs; Lee, Mark; Enver, Necati; Sulica, Lucian (The Laryngoscope, 2020)
The aims of this work were 1) to investigate whether office laryngoscopy is an aerosol-generating procedure with an optical particle sizer (OPS) during clinical simulation on healthy volunteers, and 2) to critically discuss methods for assessment of aerosolizing potentials in invasive interventions. Prospective quantification of aerosol and droplet generation during clinical simulation of rigid and flexible laryngoscopy. Two healthy volunteers were recruited to undergo both flexible and rigid laryngoscopy. An OPS was used to quantify aerosols and droplets generated for four positive controls relative to ambient particles (speech, breathing, /e/ phonation, and /ae/ phonation) and for five test interventions relative to breathing and phonation (flexible laryngoscopy, flexible laryngoscopy with humming, flexible laryngoscopy with /e/ phonation, rigid laryngoscopy, and rigid laryngoscopy with /ae/ phonation). Particle counts in mean diameter size range from 0.3 to >10 μm were measured with OPS placed at 12 cm from the subject's nose/mouth. None of the laryngoscopy interventions (n = 10 each) generated aerosols above that produced by breathing or phonation. Breathing (n = 40, 1-3 μm, P = .016) and /ae/ phonation (n = 10, 1-3 μm, P = .022; 3-5 μm. P = .083; >5 μm, P = .012) were statistically significant producers of aerosols and droplets. Neither speech nor /e/ phonation (n = 10 each) were associated with statistically significant aerosols and droplet generation. Using OPS to detect droplets and aerosols, we found that office laryngoscopy is likely not an aerosol-generating procedure. Despite its prior use in otolaryngological literature, an OPS has intrinsic limitations. Our study should be complemented with more sophisticated methods of droplet distribution measurement. 3 Laryngoscope, 130:2637-2642, 2020.